The Benefits and Challenges of English Teachers in Implementing E-Learning during Covid-19 Pandemic - Feira Fajar Kariena; Ratna Dewanti; Siti Drivoka Sulistyaningrum; Darmahusni Darmahusni; Sri Sumarni (Jurnal Pendidikan Bahasa dan Sastra, 2022)
This paper will present the result of a study aiming to identify teachers’ opinions about the values and challenges of an online teaching English as a foreign language during covid 19 pandemic in a vocational high school in West Java Indonesia. The study has been informed by the theory of e-learning, modify the principles of e-learning, types of e-learning, the benefits and challenges of e-learning. Using a qualitative approach, this research was a case study which involved 21 vocational high school English teachers in Bekasi. Data collection was done through an in-depth interview and questionnaire to explore teachers’ e-learning experiences, both benefits and challenges in teaching English. Based on the findings, the majority of teachers expressed that the use of e-learning was effective with various benefits and challenges such as teachers’ readiness in implementing e-learning, accessibility and Internet connectivity, low students’ participation and identify plagiarism. Thus, the researcher recommended more studies of e-learning to get practical strategies to employ online sources for education in the pandemic situation.